2016
DOI: 10.18176/jiaci.0036
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Rhinometry in Nasal Provocation Tests in Children and Adolescents

Abstract: Objectives: To standardize acoustic rhinometry (AR) in nasal provocation tests (NPTs) with histamine in children and adolescents. Patients and Methods: We performed a cross-sectional validation to compare AR with anterior active rhinomanometry (AAR) during histamine NPT in 20 children and adolescents with persistent allergic rhinitis and 20 controls. Changes in total nasal resistance (AAR) were compared with changes in nasal volume in the first 5 cm (V5 ; P=.04) at baseline. The mean histamine concentration ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…These results are also consistent with previous findings. In addition to our studies using acoustic rhinometry for NPT [ 2 , 8 - 11 ], Wandalsen et al [ 12 ] also found that acoustic rhinometry was an effective measure for NPT in adolescents and children. The current study is the first to perform the NPT according to the standardized protocol in the EAACI position paper and to measure the changes in these objective parameters.…”
Section: Discussionsupporting
confidence: 54%
“…These results are also consistent with previous findings. In addition to our studies using acoustic rhinometry for NPT [ 2 , 8 - 11 ], Wandalsen et al [ 12 ] also found that acoustic rhinometry was an effective measure for NPT in adolescents and children. The current study is the first to perform the NPT according to the standardized protocol in the EAACI position paper and to measure the changes in these objective parameters.…”
Section: Discussionsupporting
confidence: 54%
“…79 Recently, acoustic rhinometry was validated as a technique for monitoring NPT with histamine in children and adolescents, and compared it with the previous acoustic rhinomanometry. 10…”
mentioning
confidence: 99%
“…[7][8][9] Recently, acoustic rhinometry was validated as a technique for monitoring NPT with histamine in children and adolescents, and compared it with the previous acoustic rhinomanometry. 10 One of the biggest obstacles to the implementation of specific NPT routine investigation and evaluation of patients with rhinitis symptoms is the high cost and test duration, both being directly proportional to the number of concentrations of the provocative agent used.…”
mentioning
confidence: 99%
“…Nasal patency can be evaluated subjectively using symptom severity scales [4][5][6] or objectively using clinical measures [7], such as acoustic rhinometry, a validated noninvasive tool applied to measure the area and volume of the nasal cavity [8]. In children, measurement of volume in the anterior part of the nose has been shown to be sensitive for changes in nasal patency due to changes in mucosal swelling after the nasal provocation test [9] and after decongestion [10]. Nasal cytology can also be used for objective evaluation of mucosal inflammation and provides insights into the efficacy of therapeutic interventions [11,12].…”
Section: Introductionmentioning
confidence: 99%